PENGARUH KETERAMPILAN DAN KEMAMPUAN KERJA TERHADAP KINERJA KARYAWAN PADA NADIRA HIJAB DI KABUPATEN BEKASI - Riani, Lince Fadhilah; Sutrisno, Niantoro (JAB (Jurnal Akuntansi & Bisnis), 2021)
This study aimed to determine the effect of the independent variable on the dependent variable, namely Skills and Work Ability on employee performance at Nadira Hijab, a Muslim clothing SME company located in Bekasi Regency. The number of respondents who are used as research objects is 36 people, this number is the total population as well as the sample or saturated sample. The data analysis method used in this research is descriptive analysis with a quantitative approach through classical assumption test and multiple linear regression analysis. The results showed that: (1) There is a partial effect of Skills (X1) on Employee Performance (Y) on Nadira Hijab in Bekasi Regency. (2) There is a partial effect of Work Ability (X2) on Employee Performance (Y) on Nadira Hijab in Bekasi Regency. (3) There is a simultaneous influence of Skills (X1) and Workability (X2) on Employee Performance (Y) at Nadira Hijab in Bekasi Regency.Â Keyword: Skill, Work Ability, Employee Performance